CHEMISTRY AND ITS PROPERTIES - Botirova Sayyora (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The material world around us is made up of bodies. They differ in size, color, mass, shape and other characteristics. What they use for a purpose is called a buy urn. The fact that objects have different properties depends primarily on their composition. The components of the body are called substances.